Antiseptic Irrigation Solutions Used in Total Joint Arthroplasty: A Critical Analysis Review. Issue 3 (March 2022) - Christopher, Zachary K.; Deckey, David G.; Pollock, Jordan R.; Spangehl, Mark J.
Abstract : There are limited data that directly compare the efficacy of antiseptic irrigation solutions used for the prevention and treatment of periprosthetic joint infections in orthopaedic procedures; there is a notable lack of prospective data. For prevention of periprosthetic joint infections, the strongest evidence supports the use of low-pressure povidone-iodine. For the treatment of periprosthetic joint infections, delivering multiple solutions sequentially may be beneficial.